Dengue illness impacts daily human mobility patterns in Iquitos, Peru. - Kathryn L Schaber; Valerie A Paz-Soldan; Amy C Morrison; William H D Elson; Alan L Rothman; Christopher N Mores; Helvio Astete-Vega; Thomas W Scott; Lance A Waller; Uriel Kitron; John P Elder; Christopher M Barker; et al. (Public Library of Science (PLoS), 2019)
BACKGROUND:Human mobility plays a central role in shaping pathogen transmission by generating spatial and/or individual variability in potential pathogen-transmitting contacts. Recent research has shown that symptomatic infection can influence human mobility and pathogen transmission dynamics. Better understanding the complex relationship between symptom severity, infectiousness, and human mobility requires quantification of movement patterns throughout infectiousness. For dengue virus (DENV), human infectiousness peaks 0-2 days after symptom onset, making it paramount to understand human movement patterns from the beginning of illness. METHODOLOGY AND PRINCIPAL FINDINGS:Through community-based febrile surveillance and RT-PCR assays, we identified a cohort of DENV+ residents of the city of Iquitos, Peru (n = 63). Using retrospective interviews, we measured the movements of these individuals when healthy and during each day of symptomatic illness. The most dramatic changes in mobility occurred during the first three days after symptom onset; individuals visited significantly fewer locations (Wilcoxon test, p = 0.017) and spent significantly more time at home (Wilcoxon test, p = 0.005), compared to when healthy. By 7-9 days after symptom onset, mobility measures had returned to healthy levels. Throughout an individual's symptomatic period, the day of illness and their subjective sense of well-being were the most significant predictors for the number of locations and houses they visited. CONCLUSIONS/SIGNIFICANCE:Our study is one of the first to collect and analyze human mobility data at a daily scale during symptomatic infection. Accounting for the observed changes in human mobility throughout illness will improve understanding of the impact of disease on DENV transmission dynamics and the interpretation of public health-based surveillance data.